Urinary Level of Interleukin-8 in Acute Pyelonephritis - Eskandarifar, Alireza; Seyedzadeh, Seyed abolhassan (Journal of Pediatric Nephrology, 2021)
Backgroundand Aim: urinary tract infection is a prevalent disease in children. Determining the location of the bacterial invasion has a great impact on the treatment, follow-up, and complications. For this purpose, different laboratory and imaging methods are used, which are often invasive or unavailable. One of the non-invasive methods is to measure biomarkers such as interlukin-8 (IL-8) in the urine.The aim of this study was to evaluate the urinary level of interleukin-8 in acutepyelonephritis. Methods: This cross- sectional study was carried out on 50 children aged 3-60 months. The children were divided into two groups. The first group included children with acute pyelonephritis and the second group included healthy children who were randomly selected as controls. Then, the urine levels of IL-8 and creatinine were measured. Results: The mean age of the subjects in case and control groups was 17.5 ± 22 and 22.5 ± 18.2 months, respectively (P = 0.92). The mean urinary ratio of IL- 8/Cr in the patient and control groups was 161.7 ± 90.1 and 12.2 ± 19.6 Pgr/mgr respectively, indicating a significant difference (P = 0.03). The results showed that a urinary IL-8/Cr ratio of 32 pg/mg was diagnostic according to the Receiver Operating Curve (ROC). Conclusion: Urinary IL-8/Cr ratio can be used for early diagnosis of acute pyelonephritis